Left behind: Naomi Mitchison's Cloud Cuckoo Land (1925) and the women of ancient Greece and the First World War. (8th November 2017) - Bridges, Emma
Abstract: Classical allusions in the works of the female poets and authors writing during and immediately after the First World War are scarce. A notable exception is Naomi Mitchison's 1925 historical novel Cloud Cuckoo Land, in which, against the backdrop of the last years of the Peloponnesian War in the fifth century BCE, Mitchison tells the story of a young couple forced into exile. Written at a time when war in Europe was a recent memory, the novel examines political and ideological conflict, gender roles, and the impact of war on domestic life. This article examines the ways in which Mitchison, a fervent campaigner for women's rights, draws on the ancient setting, and the author's knowledge of Greek political and social history, to bring her readers' attention to deeply problematic elements of the experiences of her contemporaries — in particular women's inability to exercise control over either the wider political situation or the path of their own lives, this latter being closely linked to their lack of bodily autonomy.